Trends in diabetes and pre-diabetes prevalence and diabetes awareness, treatment and control across socioeconomic gradients in rural southwest China. (28th July 2017) - Cai, Le; Li, Xiao; Cui, Wenlong; You, Dingyun; Golden, Allison Rabkin
Abstract: Background: This study aimed to determine trends in pre-diabetes and diabetes prevalence and diabetes awareness, treatment and control across socioeconomic gradients in rural southwest China. Methods: Data were collected from two cross-sectional health interviews and examination surveys among individuals aged ≥35 years in rural China. Fasting blood sugar levels were measured for each participant. Results: From 2009 to 2016, the overall prevalence of pre-diabetes and diabetes increased from 8.4 and 7.7% to 19.0 and 9.5%, respectively, while awareness, treatment and control of diabetes increased from 32.7, 20.0 and 6.1% to 49.3, 32.1 and 13.5%, respectively ( P < 0.01). Participants with higher annual incomes had higher diabetes prevalence and treatment levels than their counterparts and showed a remarkably high increase in rate of pre-diabetes ( P < 0.01). Whereas prevalence of pre-diabetes and diabetes increased across all ethnic groups during the study period, increased rates of diabetes awareness, treatment and control were only observed among Han Chinese ( P < 0.01). Diabetic patients with higher levels of education had higher awareness, control and treatment of diabetes than their counterparts ( P < 0.05). Conclusions: The prevalence of pre-diabetes and diabetes and the level of diabetes awareness, treatment and control increased substantially across all socioeconomic gradients in rural southwest China.